Surveillance for Shiga Toxin–producing Escherichia coli, Michigan, 2001–2005 - Manning, Shannon D. (Centers for Disease Control and Prevention, 2007)
A surveillance system used different detection methods to estimate prevalence of Shiga toxin–producing Escherichia coli during 2003–2005 and 2001–2002. More non-O157 serotypes were detected by enzyme immunoassay than by evaluation of non-sorbitol–fermenting E. coli isolates. We therefore recommend use of enzyme immunoassay and culture-based methods.